MODERNISASI PARTAI POLITIK DI ERA 4.0 - Arsyi Arsyi (Al-Ijtima`i: International Journal of Government and Social Science, 2022)
In a democracy, the presence of political parties is very much needed. Political parties act as the backbone for the journey of democracy in Indonesia, because political partiesplay arole in the political process in the legislativebody, government, and other related institutions. The existence of political parties is increasingly important for channeling collective will - presenting the interests of various groups in society that are held in general elections. Modernization of political parties refers to the process of development and evolution from lower levels to higher levels. Modernization has the meaning of transformation which means a change in the existing system in a country caused by the progress of globalization that involves changes in politics, social structure, culture and economic growth. Modernization of political parties is the dynamics of political modernization which implies a process of increasing complexity of human problems that require political action. In general, it can be said that politics is a matter that includes the differentiation of roles as well as integrating the organizational structure. The modernity of the role and organizational structure of politics implies the existence of political parties that act as a link between the public and the government. Community Participation in the 4.0 era also provides opportunities for increased political participationin campaigning on social media, where campaigns carried out through social media have different valuesfrom traditional campaigns. Modernization of political parties provides opportunities and obstacles that can facilitate the realization of a democratic government system. Modernization of political parties can increase public participation in transparently viewing the proposed political party but unlimited information can also be one of the problems that will destabilize unity due to hate speech among political parties or communities of political parties aimed at related political opponents.